Serum Biomarkers AFP, CEA and CA19-9 Combined Detection for Early Diagnosis of Hepatocellular Carcinoma - Muhammad Ibrahim Alhadi EDOO; Vikram Kumar Chutturghoon; Gyabaah Kwabena WUSU-ANSAH; Hai ZHU; Tao Yang ZHEN; Hai Yang XIE; Shu-Sen ZHENG (Tehran University of Medical Sciences, 2019)
Background: We aimed to evaluate the whether AFP levels alone is an adequate screening indicator, or a combination of Generally, alpha-fetoprotein (AFP), CA19-9 and CEA could provide a better diagnostic tool in detecting and screening asymptomatic patients with primary hepatic cancer (PHC), and also evaluate the correlation of degree of differentiation with serum biomarker levels. Methods: We retrospectively reviewed the medical records of 1362 patients form 2014-2018 who visited the first Affiliated Hospital of Zhejiang University, Hangzhou, China for health check-ups or were diagnosed with cancer or cirrhosis. We then analyzed preoperative tumor markers level of AFP, CA19-9, and CEA. The standard reference values (AFP ≤20 ng/L CEA ≤ 5 ng/L, and CA19-9  ≤ 37 U/mL) were as positive or negative cut off values. Further, the histological sections of patients were categorized and correlated them with the three serum biomarkers. Results: Serum AFP, CEA, and CA19-9 levels in the PHC group were significantly higher compared to those with liver cirrhosis and healthy control groups (P < 0.03). With AFP as a single tumor marker for PHC diagnosis, it had a sensitivity of 63.3% with a specificity of 80.8%. AFP combined with CA19-9 and CEA showed specificity of 100%, a sensitivity 2.5% with the positive and negative predictive values of 100% and 22% respectively. Furthermore, histological evaluation revealed the highest AFP level of 9366.14±23902.61 ng/L associated with poorly differentiated HCC, while well-differentiated HCC, had the lowest mean AFP level of 45.19±181.27 ng/L. Conclusion: Combined serum levels of AFP, CA19-9  and CEA does not provide a superior advantage over AFP alone as a screening and diagnostic tool for HCC detection.